Impact of group discussion on student’s performance in biology (A case study of Heyik secondary school in Kaduna south local government area of Kaduna Nigeria) - Kingsley Peace Ifeoma (Journal of Education, Social & Communication Studies, 2025)
This study assessed the impact of group discussions on students' academic performance in biology at Heyik Secondary School, Kaduna. The main objective was to explore how group discussions influenced students' understanding of biology, identify factors affecting their effectiveness, and address challenges like time management. Grounded in Behaviourism, Constructivism, Connectivism, and Experiential Learning Theories, the study used a survey design with 150 randomly selected senior secondary students. Data were collected via questionnaires and analyzed using SPSS, with descriptive statistics and correlation analysis to examine the relationships between group discussions, communication, and student performance. The findings showed a positive and significant correlation between communication within group discussions and improved biology performance. Both learning and development were also positively correlated with better academic outcomes, suggesting that group discussions enhance comprehension and retention. However, time management emerged as a key challenge, with scheduling conflicts and inefficient use of time limiting the benefits. The study recommends that educators focus on enhancing communication strategies, incorporating modern tools, and promoting continuous learning through curriculum and extracurricular activities. Continuous monitoring and evaluation, with regular assessments, will help refine communication and time management strategies based on student feedback and performances.